Doenças diarreicas agudas e a qualidade da água na aldeia Trocará (Tucuruí/Pará/Brasil): um estudo estatístico - GONÇALVES, Marcos Barradas (2021)
This study sought to trace associations between the quality of water for human consumption distributed to the Trocará village in the municipality of Tucuruí, PA, and the occurrence of cases of Acute Diarrheal Diseases (DDA). The water quality data were provided by the Special Indigenous Health Secretariat (SESAI), and the records of ADD cases were made available by the Epidemiological Surveillance Department of the municipality, through the Acute Diarrheal Disease Monitoring Program (MDDA), and correspond to the period from January 2018 to December 2020. The type of study adopted was of the ecological type, and used tools of correlation analysis, univariate and multivariate through linear regression statistics. The occurrence of DDA was higher among individuals aged 1 to 4 years. With the analyses performed, it was possible to observe high correlations between the cases of DDA and the quality of water consumed by the population, especially in the multivariate analysis, and the highest correlation values were found using one week of time lag, with R² values reaching 0.61, and in the correlation analysis the parameters with the highest correlation coefficients were turbidity and E. Coli, with R² reaching 0.655. The results show a direct relationship between the quality of the water supplied to the population and the cases of DDA, requiring measures that can improve the issue in question.